BLOwing Trees to the Ground: Layout Optimization of Decision Trees on Racetrack Memory - Hakert, Christian; Khan, Asif Ali; Chen, Kuan-Hsun; Hameed, Fazal; Castrillon, Jeronimo; Chen, Jian-Jia (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
Modern distributed low power systems tend to integrate machine learning algorithms, which are directly executed on the distributed devices (on the edge). In resource constrained setups (e.g. battery driven sensor nodes), the execution of the machine learning models has to be optimized for execution time and energy consumption. Racetrack memory (RTM), an emerging non-volatile memory (NVM), promises to achieve these goals by offering unprecedented integration density, smaller access-latency and reduced energy consumption. However, in order to access data in RTM, it needs to be shifted to the access port first, resulting in latency and energy penalties. In this paper, we propose B.L.O. (Bidirectional Linear Ordering), a novel domain-specific approach for placing decision trees in RTMs. We reduce the total amount of shifts during inference by exploiting the tree structure and estimated access probabilities. We further apply the state-of-the-art methods to place data structures in RTM, without exploiting any domain-specific knowledge, to the decision trees and compare them to B. L.O. We formally prove that the B.L.O. solution has an approximation ratio of 4, i.e., its number of shifts is guaranteed to be at most 4 times the optimal number of shifts for a given decision tree. Throughout the experimental evaluation, we show that for the realistic use case B.L.O. empirically outperforms the state-of-the-art data placement method on average by 54.7% in terms of shifts, 19.2% in terms of runtime and 19.2% in terms of energy consumption.